Penyelesaian Sengketa Ekonomi Syariah Melalui Arbitrase: Konsep, Kewenangan, dan Implementasi - Imam Khoirul Fahmi (Ekonosfera: Jurnal Ekonomi, Akuntansi, Manajemen, Bisnis dan Teknik Global, 2025)
The resolution of disputes in sharia-based economic activities has become an urgent need in line with the rapid development of Islamic finance and business practices in Indonesia. Arbitration is regarded as an alternative dispute resolution mechanism that is more effective than conventional litigation because it offers a process that is fast, flexible, confidential, and capable of ensuring compliance with sharia principles. This article discusses the concept of arbitration from the perspective of Islamic economic law, including its definition, fundamental principles, and its differences from conventional judicial mechanisms. In addition, this article analyzes the duties and authorities of sharia arbitration institutions, particularly in issuing final and binding decisions. To demonstrate its effectiveness, this study presents a case study of sharia economic dispute resolution through arbitration and identifies the factors contributing to its success. The findings show that arbitration plays a strategic role as a dispute resolution forum that not only provides legal certainty but also preserves the integrity of sharia muamalah principles. This article recommends strengthening sharia arbitration institutions, enhancing the competence of arbitrators, and optimizing outreach regarding arbitration mechanisms to sharia business actors so that dispute resolution in the Islamic economic sector can be more effective and just.